Shareholder value implications of supply chain ESG: evidence from negative incidents - Lin, Xuanpu; She, Guoman; Yoon, Aaron; Zhu, Haoran (Review of Accounting Studies, 2025)
Using a novel measure that captures negative ESG incidents at both listed and private suppliers, we provide large-scale evidence on the value implications of supply chain ESG. We find that firms with fewer supply chain ESG incidents exhibit higher future accounting performance and that this effect is stronger in the presence of more conscious customers and vulnerable supply chains. We also find that firms with robust supply chain ESG exhibit higher future stock returns and that this effect is more pronounced when information frictions are higher, which suggests that it takes time for the market to understand the value implications of supply chain ESG. Overall, we highlight the benefits of managing supply chain ESG and the decision usefulness of the related information.